Resilience, Emotional Well-Being, and Student Engagement: Keys to School Transformation in the Post-COVID Era - Fernández-Terol, Lucia; Segovia, Jesús Domingo; Díaz Delgado, Miguel Ángel; Olmo Extremera, Marta (Revista Saberes Educativos, 2025)
In response to the challenges posed by the pandemic of COVID 19, this article reports on a study carried out on a school that managed to maintain school success and reinvent itself in the post-pandemic period. In this study a qualitative methodology was employed, using a case study with eleven participants in a school operating as a Professional Learning Community. Findings highlighted resilience and emotional well-being as a key component of care and learner engagement and a driver for preventing dropout. Professional reflection at critical moments provided new perspectives for addressing and transforming reality, alongside distributed leadership. The findings have significant implications for the design of school strategies that promote resilience, emotional well-being, student engagement and leadership offering valuable guidance for other educational institutions seeking to adapt and transform effectively in times of crisis.